Qingxuan Runmu Yin alleviates dry eye disease via inhibition of the HMOX1/HIF-1 pathway affecting ferroptosis - Wang, Jiadi; Liu, Yue; Zong, Beiting; Zhao, Shanshan; Li, Yue; Zhang, Zhirui; Yao, Jing (Frontiers in Pharmacology, 2024)
The prevalence of dry eye disease (DED), a multifactorial ocular surface disease characterized by tear film instability, is increasing yearly. Qingxuan Run Mu Yin (QXRMY) is a traditional Chinese medicine(TCM)consisting of Radix Rehmanniae, Radix Scrophulariae, Rhizoma Atractylodis macrocephalae, Herba Dendrobii, Flos Lonicerae, Forsythia suspensa, Ophiopogon japonicus, Saposhnikovia divaricata, Radix Platycodi, and Radix Glycyrrhizae. It has excellent therapeutic effects on dry eye syndrome and a good anti-inflammatory effect on immune-related inflammation.However, the molecular mechanism of Qing Xuan Run Mu Yin in treating dry eye syndrome is largely unknown. The present study used an online database to identify potential target genes of QXRMY for treating DED. The possible mechanisms of these target genes for the treatment of DED were obtained through Gene Ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) databases, Hub genes screened by Cytoscape and intersected with ferroptosis-related genes, and the essential genes were finally obtained based on the results of the analyses. DED cell model and rat model were constructed in this study to validate the critical genes and pathways, and it was confirmed that QXEMY alleviated DED by repressing ferroptosis through inhibiting the HMOX1/HIF-1 pathway. In conclusion, this study integrated network pharmacological analyses and experimental validation to provide an effective method to investigate the molecular mechanism 2 of QXRMY in treating DED.